Revisiting Hydration and Water Scarcity: Technological Advances and Molecular Resonance Effect Technology (MRET) Activation - Smirnov, Igor; Fisher, Howard (European Journal of Applied Sciences, 2025)
The concept of global water scarcity requires reexamination in light of recent technological advancements, such as solar desalination and Molecular Resonance Effect Technology (MRET). While water covers approximately 70% of the Earth’s surface, the potential for freshwater generation through solar desalination, alongside innovations in hydration technology, offers new opportunities for addressing the growing concern of water scarcity. This article explores the role of water in human health, the physiological implications of hydration, and the innovative benefits of MRET-activated water in improving hydration efficiency. Furthermore, we examine the potential of MRET technology to promote longevity and enhance overall physiological function.